Critical success factors for smart-professional disruptor in university - Phisit Pornpongtechavanich; Kawitsara Eumbunnapong; Therdpong Daengsi; Prachyanun Nilsook (Institute of Advanced Engineering and Science, 2022)
Current and emerging technologies have changed a lot. Consequently, every year, Gartner Technology has made many new changes in accordance with global developments. For example, in terms of artificial intelligence (AI), mixed reality (MR), extended reality (XR), collaboration platforms, online learning, distributed cloud, internet of behaviors (IoB), and cybersecurity. Due to changes in technology, disruptors have to constantly learn new technology in order to be up to date in the transfer of knowledge to learners. Therefore, in this research, critical success factors (CSFs) have been studied, which help them become highly skilled professionals by developing their own skills with technology to be a successful disruptor at university. The study found the CSFs, which were derived from the synthesis of international research papers. Disruptors' success consists of 12 internal and 10 external success factors. Smart-professional disruptors in universities were assessed using a focus group method with eight experts. Focus group results found that there were seven important internal factors for smart-professional disruptors in universities and seven minor internal factors. Including all internal factors, smart-professional disruptors have 14 factors; external factors are the most important ones for smart-professional disruptors in universities. In total, smart-professional disruptors have a total of 11 external factors.